On international monetary order: agenda for action, by a group of monetary experts - Graduate Institute of International Studies (Geneva, Switzerland) (Geneva : Graduate Institute of International Studies, 1968)
This book contains Reports and papers presented at the Conference on International Monetary Order, Geneva, April 18-20, 1968 which was centered on Special Drawing Right as a solution for the stabilization of currencies.
Organized by the Graduate Institute of International Studies.
Bibliographical footnotes and index
usc 04/10/18
Loans
Keywords: Foreign exchange; Balance of payments; Currency question